Barriers to the Adoption of Social Media Technology in the domain of Social Customer Relationship Management in Travel Agencies - Alizadeh, Fereshteh; Ahmadi, Fatemeh; Basiri, Zeinab (International Journal of Engineering and Technology, 2018)
In today’s world, social networks play a very important role in relationships among people throughout the world. The popularity of social networks has increased among Iranian users as they became a place to explore different individual desires and interests. Thus, these networks are now an integral part of the lives of many people in our society. Integrating these two categories may be considered as a key business strategy which has caught the attention of many service organizations in developed countries.Therefore, to identify the barriers to the adoption of social networks in travel agencies for improving the adoption of networks in order to ameliorate CRM policies in organizations after deriving the effective factors mentioned in previous studies and utilizing Exploratory Factor Analysis (EFA) to explore the most common barriers in this field, three hypotheses were formulated and the population of service organizations and some of their customers in Tabriz with a 245-member sample were selected for the study and a Likert scale questionnaire was designed and distributed among the members of the study sample. The study results had a high validity and reliability and the LISREL, a structural equation modeling application, was used to carry out the Confirmatory Factor Analysis (CFA) and to discover a model from the effective factors. Results showed that legal and technological factors as barriers to the adoption of social networks for CRM had the largest impact in Iran.